ChemInform Abstract: Regioisomeric 4‐Amino‐ and 6‐Aminopyrazolo[3, 4‐b]pyridines: Synthesis and Structure Determination by NMR Spectroscopy and X‐Ray Diffraction. Issue 25 (3rd June 2013) - Petrov, A. A.; Kasatochkin, A. N.; Emelina, E. E.; Haukka, M.
Abstract Heating 5‐aminopyrazoles (I) with ethoxymethylidenemalononitrile in refluxing MeOH selectively affords 4‐aminopyrazolopyridines (III).